2015
DOI: 10.7824/rbh.v14i4.454
|View full text |Cite
|
Sign up to set email alerts
|

Características fisiológicas do feijoeiro cultivado em solos após fitorremediação do picloram

Abstract: A fitorremediação tem sido relatada como técnica promissora para a descontaminação de solos com resíduos de herbicidas. Para herbicidas hormonais, há dificuldade na determinação de resíduos pela técnica do bioensaio em função da variação na resposta em crescimento apresentada pela indicadora. Objetivou-se com esse trabalho avaliar o efeito de subdoses do picloram, em solos fitorremediados com braquiária, nas características fisiológicas do feijoeiro. O ensaio foi realizado em ambiente protegido no delineamento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, this morphological trait increased with phytoremediation by the Urochloa sp. (Franco et al, 2015). Belo et al (2016) reported similar trend for the dry mass of P. glaucum after phytoremediation by C. juncea and C. ensiformis.…”
Section: Performance Of C Juncea As Bioindicator Of Phytoremediationmentioning
confidence: 54%
“…However, this morphological trait increased with phytoremediation by the Urochloa sp. (Franco et al, 2015). Belo et al (2016) reported similar trend for the dry mass of P. glaucum after phytoremediation by C. juncea and C. ensiformis.…”
Section: Performance Of C Juncea As Bioindicator Of Phytoremediationmentioning
confidence: 54%
“…The excess of Cu can cause damage to the photosynthetic apparatus (Gonzá lez-mendoza et al, 2013), andchanges in photosynthesis may represent the physiological state of the plant (Kalaji et al, 2016) Environmental stresses can interfere with the efficiency of photosynthesis and inactivate PS II-photosystem II (P680) and the electron transport chain for the production of ATP and NADPH2 (Costa et al, 2003). Fluorescence analysis has advantages for studies of electron transport during photosynthesis and it is possible to record electron transport in photosystem II (Franco, 2015). THE application of exogenous nitric oxide-NO can mitigate the decrease in photosynthetic capacity in plants, caused by a variety of abiotic stresses (Wang et al 2014 ), is able to diffuse through membranes (Lamattina & Garcí a Mata, 2016), is a molecule that acts as a signaler involved in the regulation of plant growth and development, in defense against pathogens and in responses to abiotic stress (Sanz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%